CONSTRUCTING THE VISUAL LANGUAGE OF 19TH CENTURY CELEBES SEA REGION MARITIME CULTURE THROUGH CONCEPT ART - Christian Aditya (Universitas Multimedia Nusantara, 2020)
In order to create a believable world for the animated content. Concept art for the animation are created through the process of studying literatures about Celebes Sea maritime history and field observation on Celebes Sea region. In this paper, the concept art being discussed is limited to the environment of the animated world along with some of Its property such as houses and boat, however there are minimum visual data on related literature and unmaintained artifacts / model from field observation. There- fore, visual language has to be decoded through historical text in the literature and also through visual research on available artifacts / model of the property. The concept art development is still an ongoing process.